Designing Geoscience Learning for Sustainable Development: A Professional Competency Assessment for Postgraduate Students in Science Education Program - Eko Hariyono; Abadi Abadi; Liliasari Liliasari; Agus Fani Candra Wijaya; Hiroki Fujii (Universitas Negeri Surabaya, 2018)
This research involved 19 postgraduate students majoring on Science Education at one university in Surabaya who were programming Earth and Space Sciences course. The objective of this research is to measure students ability in designing a lesson plan for sustainable education on environmental issues around volcanoes by integrating education for sustainable development (ESD) competence. Descriptive quantitative analysis was employed to assess the lesson plans developed by the students. In general, the results showed that the lesson plans were less contextual to support the improvement of decision-making abilities on the environmental issues, the emergence of environmental awareness among students, encouragement to the students to have sense of belonging to the environment, and fostering critical analysis of various environmental phenomena. The results suggest further efforts to improve professional competence of the postgraduate students in developing geoscience learning instruments, particularly related to integrate the ESD competence into lesson plans.